Comparison of Intermittent Epidural Bolus and Continuous Epidural Infusion for Postoperative Pain Management in Abdominal Surgery Patients - Siswagama, Taufiq Agus; Asmoro, Aswoco Andyk; Subagyo, Houdini Pradanawan; Laksono, Buyung Hartiyo (Faculty of Medicine, Brawijaya University, 2024)
Background: Abdominal surgery often leads to high postoperative pain scores, which are commonly managed using epidural analgesia through either continuous infusion or intermittent bolus administration. This study aimed to compare the effectiveness of intermittent epidural bolus and continuous epidural infusion in managing postoperative pain among patients who underwent abdominal surgery.Methods: This cross-sectional study included 90 patients who underwent abdominal surgery and were randomly assigned to two groups. Group one received intermittent epidural bolus analgesia with ropivacaine 0.1875% and fentanyl 50 µg, administered as 10 cm³ every 8 hours (n=45). Group two received continuous epidural infusion analgesia with ropivacaine 0.1875% and fentanyl 100 µg, in a total volume of 50 cm³ at a rate of 3 cm³/hour (n=45). Pain levels were assessed using the numerical rating scale (NRS) at rest and during movement, measured every 12 hours for 84 hours. Statistical analysis was conducted using the independent t-test with a significance level of α=0.05 and a 95% confidence interval.Result: At 24 hours postoperatively, the NRS at rest was significantly lower in the continuous infusion epidural (0.15 ± 0.36) compared to the intermittent bolus (0.91 ± 0.35) (p=0.000), and this trend persisted at subsequent time points (36, 48, 60, 72, and 80 hours postoperatively). For movement, the NRS at 36 hours was also lower in the continuous infusion epidural (1.00 ± 0.00) compared to the intermittent bolus (1.29 ± 0.45) (p=0.000), with similar differences observed at other time points.Conclusion: Continuous epidural infusion provides superior analgesia to intermittent epidural bolus administration in abdominal surgery patients. This method is associated with faster and sustained reductions in pain intensity at rest and during movement.